Idle Expenditure on Establishment of Trauma Care Centres in Maharashtra - CAG of India (CAG of India)
Trauma Care Centre at Vaijapur, District Aurangabad was not operational since last six years for want of electric supply resulting in idle expenditure of INR 1.66 crore.